Melatonin Alleviates Age-Associated Endothelial Injury of Atherosclerosis via Regulating Telomere Function - Xie Y; Lou D; Zhang D (Dove Medical Press, 2021)
Yinghua Xie,1,* Danfei Lou,2,* Daimin Zhang3 1Department of Geriatrics, Fuzhou NO.1 Hospital Affiliated with Fujian Medical University, Fuzhou, Fujian, 350009, People's Republic of China; 2Department of Geriatrics, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People's Republic of China; 3Department of Cardiology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210006, People's Republic of China*These authors contributed equally to this workCorrespondence: Daimin ZhangDepartment of Cardiology, Nanjing First Hospital, Nanjing Medical University, NO. 68 Changle Road, Nanjing, Jiangsu, 210006, People's Republic of ChinaTel/Fax +86 25-52271341Email zhangdmun@126.comBackground: Atherosclerosis is an aging-related disease, partly attributed to telomerase dysfunction. This study aims to investigate whether telomere dysfunction-related vascular aging is involved in the protection mechanism of melatonin (MLT) in atherosclerosis.Methods: Young and aged ApoE−/− mice were used to establish atherosclerotic mice model. H&E staining and immunofluorescence assay were performed to detect endothelial cell injury and apoptosis. Inflammatory cytokines and oxidative stress-related factors were determined using corresponding commercial assay kits. Telomerase activity was detected by TRAP assay, and SA-β-gal staining was conducted to evaluate cellular senescence. HUVECs were treated with H2O2 for 1 h to induce senescence. Western blot was performed to measure protein expression.Results: An obvious vascular endothelial injury, reflected by excessive production of inflammatory cytokines, elevated ROS, MDA and SOD levels, and more apoptotic endothelial cells, was found in atherosclerotic mice, especially in aged mice, which were then greatly suppressed by MLT. In addition, telomere dysfunction and senescence occurred in atherosclerosis, especially in aged mice, while MLT significantly alleviated the conditions. CYP1A1, one of the targeted genes of MLT, was verified to be upregulated in atherosclerotic mice but downregulated by MLT. Furthermore, H2O2 induced a senescence model in HUVECs, which was accompanied with a remarkably increased cell viability loss and apoptosis rate, and a downregulated telomerase activity of HUVECs, and this phenomenon was strengthened by RHPS4, an inhibitor of telomerase activity. However, MLT could partly abolish these changes in H2O2- and RHPS4-treated HUVECs, demonstrating that MLT alleviated vascular endothelial injury by regulating senescence and telomerase activity.Conclusions: Collectively, this study provided evidence for the protective role of MLT in atherosclerosis through regulating telomere dysfunction-related vascular aging.Keywords: melatonin, atherosclerosis, telomere, vascular aging, senescence